Electrophysiological analysis of hyperkalemic cardiomyocytes using a multielectrode array system - Kentaro Kito; Masahito Hayashi; Tomoyuki Kaneko (Biophysics and Physicobiology)
The action potential of cardiomyocytes is controlled by electrolytes in serum such as Na+, K+ and Ca2+. Hyperkalemia, which refers to an abnormally high concentration of K+ in the blood, can induce lethal arrythmia. In this study, the extracellular potentials on a sheet of chick embryonic cardiomyocytes were investigated at increasing K+ concentrations using a multielectrode array system. We observed that the interspike interval (ISI) was prolonged by approximately 3.5 times; dV/dt (the slope of a waveform) was decreased by more than five times; the field potential duration (FPD) was shortened by 20%, and the conduction velocity was about half at 12 mM K+ against the control (4 mM K+). In calcium therapy for hyperkalemia, although the prolongation of ISI under hyperkalemic conditions was restored, the slowing of conduction velocity, the decrease in dV/dt, and the shortening of FPD were not recovered by increasing the extracellular Ca2+ concentration. These findings provide a comprehensive understanding of cardiomyocytes in hyperkalemic conditions. Electrophysiological analysis by varying the extracellular concentrations of multiple types of electrolytes will be useful for the further discussion of the results of this study and for the interpretation of the waveforms obtained by measuring the extracellular potential.